The Motherhood Penalty in China: Having A Child Increases Gender Inequality in the Labor Market - Mingxue Zhang; Lingling Hou; Yue Wang (Global Labor Organization (GLO), 2022)
Using a comprehensive individual panel dataset in China and an event study method, we examined the effects of having a child on gender inequality from the perspectives of labor market outcomes and its mechanisms. Results show that becoming a mother implies a sharp decline in labor earnings, labor market participation, working hours and wage rate, while fathers' outcomes remain unaffected. These outcomes are driven by two potential channels: career choices and social norms. After having a child, mothers have a higher likelihood for engaging in informal jobs and less possibility of being promoted if they work in the formal sector. Moreover, social norms towards gender roles lead mothers to devote more time to housework and babysit, which generate motherhood earnings penalty in labor market. Finally, well-being analysis shows that subjective happiness and life satisfaction of both males and females are barely not changed after childbirth, and females experience an increase in social status after child arrival.
Keywords: J13; J16; J22; J31; D13; 330; motherhood penalty; gender inequality; gender gap; individual earnings